MERGER AND BUSINESS CONSOLIDATION AMONG INDONESIAN’S BUMN KARYA : A STRATEGY TO AVOID FINANCIAL DISTRESS AND STRENGTHENING CAPITAL FOR LONG-TERM SUSTAINABILITY - Andriani, Ria; Tambunan, Diana; Warsono, Warsono; Herlan, Hasta (Dynamic Management Journal, 2024)
This study aims to analyze the strategic mergers proposed by the BUMN Ministry, focusing on the mergers of PT Hutama Karya with PT Waskita Karya, PT Adhi Karya with PT Nindya Karya, and PT Wijaya Karya with PT Pembangunan Perumahan. Using a descriptive research approach, the study employs quantitative analysis to evaluate financial compatibility and operational synergies among the companies involved. The findings reveal that the merger of Adhi Karya and Nindya Karya emerges as the most advantageous option, effectively combining Adhi's liquidity challenges with Nindya's strong revenue generation capabilities. Additionally, merging PT Waskita Karya with PT Hutama Karya could provide vital resources to address Waskita's financial struggles, contingent on Hutama Karya’s capacity to manage these challenges effectively. The merger of PT Wijaya Karya with Pembangunan Perumahan shows promise in leveraging Pembangunan's stability to enhance Wijaya's financial performance. In conclusion, the proposed mergers present a strategic opportunity to enhance financial stability, operational efficiency, and market competitiveness. Merging PT Pembangunan Perumahan with PT Nindya Karya capitalizes on both companies' financial strengths, while the pairing of PT Waskita Karya and PT Adhi Karya facilitates resource pooling to improve operational performance. Lastly, the merger of PT Wijaya Karya with a smaller, agile company can help mitigate its liquidity issues while harnessing the strengths of a dynamic partner. Recommendations emphasize the importance of conducting thorough due diligence to assess financial compatibility, cultural alignment, and operational synergies before finalizing mergers. Establishing clear strategic goals and integration plans is essential for ensuring successful transitions. Ongoing monitoring and evaluation post-merger will be crucial for adapting strategies and driving sustained growth and profitability in the newly formed entities.with stakeholders will be key to rebuilding trust and securing the company’s future.